Agricultural production in the African reserves of South Africa, 1918-1969 - Simkins, C.E.W. (My University, 1980)
Among scholars who would disagree on the interpretation of many aspects of South African society there appears to be a considerable measure of consensus on the course of agricultural production in the reserves during the twentieth century. Thus M. Wilson writes: 'From one (peasant) community after another, however, there is evidence of a fall in productivity after a period of early prosperity. The tale is one of increasing pressure of population on deteriorating land, and the fall was not only in productivity per head, but in the total crop produced ... The date at which the decline began varied with the area ... in the Ciskei, it began before the end of the nineteenth century; in the Transkei it was conspicuous after 1930 ... Crops were shrinking owing to erosion and the fall in fertility. Between 1921 and 1930, 640 million pounds of mealies were produced by Africans, and between 1931 and 1939, this fell to 490 million pounds ...2 And Wolpe has a parallel passage: 'By the 1920s attention was already being drawn to the deterioration of the situation in the African areas and in 1932 the Native Economic Commission Report (1930-2) commented at length on the extremely low productivity of farming on the Reserves, on the increasing malnutrition and on the real danger of the irreversible destruction of the land through soil erosion. Every subsequent Government Commission dealing with the Reserves reiterated these points and drew attention to the decline in output.Report No. 9 of the Social and Economic Planning Council (1946) showed, for example, the decline in production of the staple crops - maize and kaffircorn - during the period 1934 to 1939. Thus maize production dropped from 3.7 million bags in 1934 to 1.2 million in 1936 and then rose slowly to 3.0 million in 1939. Kaffircorn likewise declined from 1.2 million bags in 1934 to 0.5 million in 1936, rising to 0.7 million in 1939. The above-mentioned reports and numerous other studies bear witness to the everincreasing total and irredeemable destruction, through soil erosion, of vast tracts of land, to the decline of production and to the impoverishment of the people ...'3 The purpose of this study is to submit Wilson's and Wolpe's propositions about agricultural production to critical scrutiny and to offer a fuller, more systematic account of its evolution from 1918 to 1969. The temporal limits of the study were determined by the following factors: (i) 1918 was the first year in which a Union Agricultural Census was taken; these Censuses are crucial sources for the analysis which follows: (ii) this study implicitly assumes that agriculture is virtually the only form of economic activity within the reserves. During the late sixties the reserve economies started to undergo substantial restructuring and this assumption cease, to hold.
African Studies Seminar series. Paper presented March 1980
Keywords: Agriculture. Economic aspects. South Africa. Homelands. History